Vaccines for Neglected Pathogens: Strategies, Achievements and Challenges Focus on Leprosy, Leishmaniasis, Melioidosis and Tuberculosis - Christodoulides, Myron; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book reviews successes and (remaining) challenges in vaccine development for the selected Neglected Tropical Diseases (NTD) of Leprosy, Leishmaniasis, Meliodoisis and Tuberculosis, which are a continuous burden for millions of people in affected areas worldwide. Written by frontline researchers, the volume deep-dives into different vaccine strategies, provides biotechnological background information and also tackles animal models in NTD therapeutics research. By bringing together state-of-the-art expert knowledge, the book contributes to the aim of ultimately ending the epidemics of neglected tropical diseases, complying with UN Sustainable Development Goal 3, Health and Well-Being.The volume highlights the activities of the research network VALIDATE (VAccine deveLopment for complex Intracellular neglecteD pAThogEns), funded by the Medical Research Council in the UK. The four NTDs discussed in the book were selected as these are in the focus of VALIDATE$1 (Bs research. The book targets scientists and clinicians working on NTDs, as well as all readers with a background in biomedicine and interest in vaccine development. This is an open access book.s
Preface by Prof Myron Christodoulides, University of Southampton, UK.-1. Introduction chapter on the VALIDATE network -- (Prof Helen McShane, Director Oxford NIHR Biomedical Research Centre, University of Oxford, UK and Samantha Vermaak, The Jenner Institute Laboratories, Oxford, UK) -- Part I: Leprosy -- 2. Leprosy challenges to vaccine developers -- (Dr Hua Wang, University of Glasgow, UK) -- 3. Leprosy vaccine development -- (Dr Khushboo Borah, University of Surrey, UK) -- Part II: Tuberculosis -- 4. Biomarkers in tuberculosis vaccine development -- (Dr Kenneth Akwue, University of the Witwatersrand, Johannesburg, South Africa) -- 5. Tuberculosis correlates of protection (Dr Rachel Tanner, The Jenner Institute Laboratories, Oxford, UK), -- Animal models for tuberculosis (Dr. Hao Li, China Agricultural University, Beijing, China) -- 7. BCG vaccination -- (Dr Hazel Morrison, The Jenner Institute Laboratories, Oxford, UK) -- 8. Vaccination strategies for Buruli ulcer disease (Dr Rachel Simmonds, University of Surrey, UK) -- 9. Fermentation in vaccine development (BCG) (Dr. Joanna Bacon, Public Health England, UK Government, London, UK) -- Part III: Leishmaniasis: 10. Human leishmaniasis vaccination -- (Dr Ali Bordbar, Institute Pasteur of Iran, Tehran, Iran) -- 11. Aspects of human leishmaniasis vaccine use -- (Dr Olayinka Osuolale, Elizade University, Ilara-Mokin, Nigeria) -- 12. Human challenge model for developing leishmaniasis vaccines (Prof Paul Kaye, University of York, UK) -- 13. Canine leishmaniasis vaccines -- (Prof Eduardo Coelho, Federal University of Minas Gerais, Belo Horizonte, Brazil and Prof Myron Christodoulides, University of Southampton, UK) -- Part IV: Melioidosis -- 14. Vaccines for melioidosis (Prof Chiranjay Mukhopadhyay, Kasturba Medical College, Manipal, India) -- 15. West Africa burden of disease (Dr Tukur Ismail, Zamfara State Primary Healthcare Board, Gusau, Nigeria).
Keywords: Medical microbiology; Vaccines -- Biotechnology; Biomaterials; Immunology; Biotechnology; Medical Microbiology; Biomaterials-Vaccines.; Applied Immunology; Biotechnology